Palladium-catalyzed cyclization of a pyryne precursor to higher pyrenylenes [data] - Popp, Dennis; Elbert, Sven; Barwig, Chantal; Petry, Julian; Rominger, Frank; Mastalerz, Michael (Universität, 2023)
By palladium-catalyzed oligomerization reactions of pyrene-based o-trimethylsilyl triflates, larger cyclic pyrenylenes were formed with up to 10-membered rings as has been unambiguously characterized by SCXRD. Furthermore, the underlying reaction mechanism has been studied by quantum chemical calculations.
Gesehen am 24.08.2023
Keywords: Forschungsdaten; Datenbank